Brain Cell Senescence: A New Therapeutic Target for the Acute Treatment of Ischemic Stroke. Issue 8 (28th June 2022) - Baixauli-Martín, Júlia; Aliena-Valero, Alicia; Castelló-Ruiz, María; Burguete, María C; López-Morales, Mikahela A; Muñoz-Espín, Daniel; Torregrosa, Germán; Salom, Juan B
Abstract: Aging is a major risk factor for cerebral infarction. Since cellular senescence is intrinsic to aging, we postulated that stroke-induced cellular senescence might contribute to neural dysfunction. Adult male Wistar rats underwent 60-minute middle cerebral artery occlusion and were grouped according to 3 reperfusion times: 24 hours, 3, and 7 days. The major biomarkers of senescence: 1) accumulation of the lysosomal pigment, lipofuscin; 2) expression of the cell cycle arrest markers p21, p53, and p16 INK4a ; and 3) expression of the senescence-associated secretory phenotype cytokines interleukin-6 (IL-6), tumor necrosis factor α (TNF-α), and interleukin-1β (IL-1β) were investigated in brain samples. Lipofuscin accumulation was scarce at the initial stage of brain damage (24 hours), but progressively increased until it reached massive distribution at 7 days post-ischemia. Lipofuscin granules (aggresomes) were mainly confined to the infarcted areas, that is parietal cortex and adjacent caudate-putamen, which were equally affected. The expression of p21, p53, and p16 INK4a, and that of IL-6, TNF-α, and IL-1β, was significantly higher in the ischemic hemisphere than in the non-ischemic hemisphere. These data indicate that brain cell senescence develops during acute ischemic infarction and suggest that the acute treatment of ischemic stroke might be enhanced using senolytic drugs.